Inteligencia de mercados para la exportación de ponchos de lana de la empresa Milmarte ponchos ubicada en Otavalo Ecuador - Cevallos Rojas, Nicole Anahí (2025)
The wide range of export products is essential to take advantage of the competitive advantages that Ecuador has, sheep wool ponchos are considered a product with a high cultural content. The objective of this research project is to conduct a market intelligence for the export of sheep wool ponchos of the company MILMARTE located in Otavalo Ecuador, with the objective that the company Milmarte can increase its competitiveness, position itself in new market niches and generate greater economic income. The export plan aims to take advantage of the opportunity for growth in the handicraft market so that they can export directly, since the artisans themselves take their products to foreign markets in an inadequate way, that is, they do it through third parties. The market intelligence will help to improve aspects of production and marketing of the product, and to improve in these areas. After having determined the shortcomings of the company Milmarte, an analysis of the internal and external environment was carried out, to increase its strengths, also focused on proposing, solving and identifying international markets, potential customers, direct competition, in order to correct, grow and position itself in the international market, also shows the feasibility of the export plan through the analysis of manufacturing costs, revenues, expenses and profits. The project includes a study of the theoretical aspects involved in an export plan, supported with their respective bibliographic citations\; theoretical bases, also consists of the methodological development used to obtain information\; likewise shows the results of the research, and finally throws the conclusions and recommendations of the project.